SIMULATION OF PROJECTILE MOTION - SUKMANA (NIM 20206032); Pembimbing: Dr. Ing. Mitra Djamal, USEP
Physics is a branch of sciences studying about the nature and phenomena. In physics teaching, the student are trained to propose a question then find its answer based on their available information, one way to obtain the information is by using computer simulation. Simulation is a learning model that creats the similar condition as the real one in to the classroom. It's expected that simulation based learning can help students to understand the lesson easily, make them stronger to memorize and grow their usage motivation well. Besides that, the simulation usage can decrease the cost in doing experiment. So, the projectile motion in three dimensions simulation using Mathematica 6.0 yielded in this final project expected can help the students to understand the projectile motion concept. Using Mathematica 6.0, the projectile motion equation can be solved easily. The simulation program yielded can be use to show projectile motion in two and three dimensions not only for ideal condition ( without air resistance) but also for condition white air resistance that varies linierly white velocity.